2010
DOI: 10.1186/1471-2350-11-66
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of LPL, APOA5 and APOEvariant combinations on triglyceride levels and hypertriglyceridemia: results of the ICARIA genetic sub-study

Abstract: BackgroundHypertriglyceridemia (HTG) is a well-established independent risk factor for cardiovascular disease and the influence of several genetic variants in genes related with triglyceride (TG) metabolism has been described, including LPL, APOA5 and APOE. The combined analysis of these polymorphisms could produce clinically meaningful complementary information.MethodsA subgroup of the ICARIA study comprising 1825 Spanish subjects (80% men, mean age 36 years) was genotyped for the LPL-HindIII (rs320), S447X (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 39 publications
7
28
0
Order By: Relevance
“…These findings are in line with previous studies (Huang et al, 2006;Ariza et al, 2010). Moreover, our data showed that subjects with LPL GG or GC genotypes had ORs of 0.14 (95% CI = 0.01-1.23) or 0.77(95% CI: 0.41-1.42), although this effect was not statistically significant in our population, which is in agreement with previous studies (Smart et al, 2010;Gagne et al, 1999).…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in line with previous studies (Huang et al, 2006;Ariza et al, 2010). Moreover, our data showed that subjects with LPL GG or GC genotypes had ORs of 0.14 (95% CI = 0.01-1.23) or 0.77(95% CI: 0.41-1.42), although this effect was not statistically significant in our population, which is in agreement with previous studies (Smart et al, 2010;Gagne et al, 1999).…”
Section: Discussionsupporting
confidence: 94%
“…Genetic variants of APOA5 (rs662799) and APOE (rs429358, rs7412) synergistically affected serum concentrations of triglycerides (29). In simultaneous analysis of four polymorphisms of LPL (rs320, rs328, rs1801177, rs268), two polymorphisms of APOA5 (rs662799, rs3135506), and two polymorphisms of APOE (rs429358, rs7412), serum concentrations of triglycerides were significantly increased in individuals with two or three triglycerides-raising alleles among these polymorphisms (30). In addition, environmental factors, including a high-fat and high-calorie diet and physical inactivity, may affect gene-gene interactions as well as the development of dyslipidemia (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that the effect of rs662799 of APOA5 on the regulation of serum triglycerides was modulated by other genetic and environmental factors (29)(30)(31)(32). Genetic variants of APOA5 (rs662799) and APOE (rs429358, rs7412) synergistically affected serum concentrations of triglycerides (29).…”
Section: Discussionmentioning
confidence: 99%
“…These steps are all modulated by the levels and genetic variants of the apolipoproteins like C-Ⅱ, C-Ⅲ, E, A-5 [82,83] . As persons with arteriosclerosis, particularly those with PAD, have a marked endothelial dysfunction [84] , it is possible to speculate that the action of an enzyme anchored to the endothelium, as is the case of lipoprotein lipase (LPL), is reduced.…”
Section: In Type 2 Diabetesmentioning
confidence: 99%